Hippocratic Oratory - Cross, James (James Roger), 1981- author.
1 online resource (160 pages
Keywords: James Cross is a Tutor in Classical Civilisation at University College London. He completed his PhD in Classics at King's College London. His research focuses on connections between ancient medicine and literature.